Adoption of improved sheep husbandry practices among the MSSP beneficiaries inTamil Nadu - V.Ramesh and A.K.Thiruvenkadan, S. Sent hilmuthukkumaraN, K.Sivakumar (Indian Journal of Animal Production and Management, 2019)
The present study was designed to quantify the improvement in terms of animal growth, reproduction andsurvivability as well as the adoption of improved sheep husbandry practices by the MSSP beneficiariesin Tamil Nadu. A total of 116 beneficiaries spread in two districts (Salem and Karur) were interviewed withpre-tested interview schedule, before and after the intervention of the MSSP for comparing reasonableimpact of the project. The data revealed that there were maximum level of adoption in ram rotation (100Percent), periodical weighment of animals (94.8 Percent) and colostrum feeding (100 Percent). There werehigh level of adoption in vaccination and deworming (100 Percent), isolation of sick animals (96.5 Percent)and deticking (47.50 Percent). About 68.10 and 25 Percent of the respondents were in the medium and highadopter class, respectively. It can be interpreted that if the respondents flock size increases by one unit,then the chances of achiving a higher level of adoption of recommended practices, 64 Percent less likelywhile other variables are kept constant. Similarly, it could be interpreted that if the respondents grazing levelincreases by one unit, then the chances of achiving a higher level of adoption of recommended practices,97 Percent less likely while other variables are kept constant. While the farmer increases the investmentby one unit, the adoption of recommended practices could increase by the factor of 1.000 when othervariables are kept constant. Impact of this project was studied under technological and economic aspects.Majority of the respondents felt that improvement in health cover of sheep flock as a major impact.